Challenges and Opportunities in Implementing the 21st Century Skills Learning Model for Fiqh Subjects - Ari Arkanudin; Hendro Beko Ahmad; Asmuni Asmuni (Al-Bustan: Jurnal Pendidikan Islam, 2025)
In the era of globalization, education is required to adapt to the times. One way is by applying the 21st century learning model. This model can be applied in fiqh subjects to help students understand and practice Islamic teachings in a more in-depth and contextual way. This study aims to analyze the opportunities and challenges of the 21st century skill-based learning model in fiqh subjects. This study uses a qualitative approach with the type of library research and the data collection technique is content analysis. The results of the study show that the 21st century learning model has many opportunities to improve the quality of fiqh learning. However, the implementation of this model also has several challenges, such as requiring teacher preparation, and changing the mindset of students. In conclusion, the 21st century learning model has the potential to improve the quality of fiqh learning. By overcoming various challenges, this model can be an effective tool to help students become a generation that is intelligent, characterful, and ready to face future challenges.